HUBUNGAN KADAR KOLESTROL TERHADAPKEJADIAN SINDROM KORONER AKUT PADAPASIEN POLI JANTUNG DAN PEMBULUHDARAH DI RSBP KOTA BATAM - Nopri Esmiralda; Rusdani; Irfan Dwi Nugroho (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2023)
Background: Acute coronary syndrome is a collection of clinical symptoms characterized by chest pain and other symptoms caused by decreased blood flow to the heart, usually caused by atherosclerotic plaques. Cholesterol deposition on the walls of blood vessels causes blockage of blood flow which will trigger arterosclerosis. Method: This research is a type of quantitative research. This research method is analytic observation with a cross sectional approach conducted at the Batam City Corporate Body Hospital in February 2022. Data were taken from medical records. The sampling technique was total sampling with a sample size of 134 patients. The results of the study were analyzed by frequency distribution and then tested with chi-square to determine the relationship. Result: Based on the Chi Square test, the p value = 0.00 (p < 0.05) means that there is a significant relationship between cholesterol levels and the incidence of acute coronary syndrome. Conclusion: Based on the results of this study, it can be concluded that there is a significant relationship between cholesterol levels and acute coronary syndrome at the Batam City Enterprise Hospital in 2022.